2020
DOI: 10.1001/jama.2020.19124
|View full text |Cite
|
Sign up to set email alerts
|

Association of SARS-CoV-2 Test Status and Pregnancy Outcomes

Abstract: Associations of coronavirus disease 2019 (COVID-19) and pregnancy outcomes remain unclear because most studies are case reports or case series without contemporary comparators. 1 We compared pregnant persons in labor who were infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compared with those uninfected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
3
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 8 publications
8
96
3
12
Order By: Relevance
“…An increasing risk of preterm delivery and CD with increasing severity of COVID-19 has also been reported (14). A previous study from one of the including SE centers found no increased risk of severe outcomes (25), however, they included COVID-19 positive women independently of severity, which might have biased their results.…”
Section: Characteristics Of Women Admitted For Any Reason Are Shown Inmentioning
confidence: 94%
“…An increasing risk of preterm delivery and CD with increasing severity of COVID-19 has also been reported (14). A previous study from one of the including SE centers found no increased risk of severe outcomes (25), however, they included COVID-19 positive women independently of severity, which might have biased their results.…”
Section: Characteristics Of Women Admitted For Any Reason Are Shown Inmentioning
confidence: 94%
“…The effect of SARS-CoV-2 infection in pregnant women is of particular concern: population-based studies suggest that pregnant women with COVID-19 are at increased risk for severe illness compared to non-pregnant women with COVID-19 (1). SARS-CoV-2 infection during pregnancy has also been associated with increased risk of pregnancy complications such as preterm birth, premature rupture of membranes, and preeclampsia (2)(3)(4). However, the mechanisms underlying these poor outcomes are unknown, and their dependence on SARS-CoV-2 infection of the placenta remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The study compared the pregnancy outcomes of the patients infected by SARS-CoV2 to non-infected pregnant patients. They found that SARS-CoV2 does not affect the pregnancy outcomes such as preterm birth, mode of delivery, and postpartum hemorrhage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%